Banxia Baizhu Tianma decoction attenuates obesity-related hypertension. (10th February 2021) - Jiang, Yue-Hua; Zhang, Peng; Tao, Yannan; Liu, Yang; Cao, Guangshang; Zhou, Le; Yang, Chuan-Hua
Abstract: Ethnopharmacological relevance: Banxia Baizhu Tianma decoction (BBTD) is a classical representative prescription for expelling phlegm, extinguishing wind, strengthening the spleen and dissipating excessive fluid in traditional Chinese medicine (TCM). According to both TCM theory and about 300 years of clinical practice, BBTD is especially suitable for hypertensive patients of abdominal obesity and lacking physical activity. Aim of the study: The present study tried to interpret the pharmacology of the ancient formula of BBTD. Herein, we focused on the plasma metabonomics of BBTD and evaluated the effect and targets of BBTD on endothelial protective effect. Methods: Obesity-related hypertensive mice were induced by high-fat diet for 20 weeks. BBTD (17.8 g/kg) was administered intragastrically for 8 weeks, and telmisartan group (12.5 mg/kg) was used as positive drug. Body weight, blood pressure, triglyceride and cholesterol were recorded to evaluate the efficacy of BBTD in vivo . Lipid deposition in aortic roots was assessed by oil red O staining, while morphology of aortas was observed by HE staining. Ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) was performed to study the plasma non-targeted metabonomics. According to the data of metabonomics, human aortic endothelial cells (HAECs) were treated by oxidized low-density lipoprotein (ox-LDL, 50 μg/mL) with/without BBTD (2, 1 or 0.5 mg/mL). Apoptosis rate (Annexin V-FITC/PI), migration (Transwell), cytoskeleton (Phalloidin) and density of VE-cadherin (Immunofluorescence staining) were used to investigate the effect of BBTD in vitro . Transcriptome sequencing was performed (2 mg/mL BBTD vs ox-LDL) to screen the possible targets of BBTD in endothelial protection against ox-LDL. Results: BBTD effectively reduced the body weight and total cholesterol, and decreased 12.1 mmHg in SBP and 10.5 mmHg in DBP of obesity-related hypertensive mice ( P  < 0.05). BBTD attenuated lipid deposition in arterial roots and improved the morphology of aortas in vivo . Plasma metabolite profiles identified 94 differential metabolites and suggested BBTD mainly affected glycerophospholipids and fatty acyls. Bioinformatics analysis indicated sphingolipid metabolism and fluid shear stress and atherosclerosis were main pathways. Therefore, we focused on endothelial protective effect of BBTD against ox-LDL. In vitro, BBTD demonstrated endothelial protective effects, decreasing apoptosis rate, improving cell migration in dose-dependent manner and maintaining cell morphology. Transcriptome sequencing identified 251 downregulated and 603 upregulated mRNAs after 24h-BBTD treatment, which reversed 51.8% change in mRNAs (393 DE mRNAs) induced by ox-LDL. Bioinformatics analysis supported the potential of BBTD in hypertension and suggested that BBTD improved endothelial cells by targeting mainly on p53 and PPAR signaling pathways. Conclusions: BBTD attenuates obesity-related hypertension by regulating metabolism of glycerophospholipids and endothelial protection. Graphical abstract: Image 1 Highlights: 1. BBTD attenuates high-fat diet induced obesity-related hypertension in vivo. 2. BBTD modulates plasma metabolite profiles and mainly affects plasma glycerophospholipids and fatty acyls. 3. BBTD decreases apoptosis rate, improves cell migration and maintains cell morphology of HAECs in dose-dependent manner in vitro. 4. Transcriptome sequencing and bioinformatics analysis suggested BBTD demonstrates endothelial protective effects against ox-LDL by targeting mainly on p53 signaling pathway and PPAR signaling pathway.